Exploring the Impact of Cement Mortar Adhesion Strength in the Durability of Facade Systems - Jéssica Souza; Laís Pires; Ana Silva; Matheus Nascimento (Buildings)
The durability of facade coatings is often compromised by incorrect specifications and a lack of technical knowledge, leading to reduced service lives of buildings and their components. This study analyzes how key construction characteristics affect the adhesion of mortars used in facade coatings. Tensile adhesive strength tests were conducted on in-use buildings to assess the quality of mechanical resistance and overall construction performance. The analysis highlights critical factors influencing adhesion strength, including finish type, building age, and solar orientation. Cohesive failures—particularly types E and F, as defined by Brazilian standards—were prevalent, emphasizing the importance of analyzing the types of rupture when discussing the results of adhesion tests. The results highlight that, among the various factors influencing adhesion strength, the type of finish and solar orientation play a significant role. Notably, north-facing external facades are more susceptible to adhesion failures, regardless of the type of finish. However, when considering only adhesive failures (Types B, C, or D), ground orientation tends to exhibit adhesion strength values below the normative limits. These findings provide actionable insights into improving facade performance and optimizing construction processes. By identifying the variables that significantly affect bond strength, this study offers a valuable reference for better decision-making in construction and the long-term durability of building coatings.